Microtubule-associated protein tau facilitates the targeted killing of proliferating cancer cells in vitro and in a xenograft mouse tumour model in vivo - Hristodorov, D (Nature Publishing Group, 2013)
BACKGROUND: Antibody drug conjugates (ADCs) and immunotoxins (ITs) are promising anticancer immunotherapeutics. Despite their encouraging performance in clinical trials, both ADCs and ITs often suffer from disadvantages such as stoichiometrically undefined chemical linkage of the cytotoxic payload (ADCs) and the potential immunogenicity of toxins derived from bacteria and plants (ITs). METHODS: Human microtubule-associated protein tau (MAP) was cloned in-frame with human EGF, expressed in E. coli and purified by standard chromatographic methods. The in vitro activity was confirmed by flow cytometry, cell viability assays and tubulin polymerisation assay. The in vivo efficacy was demonstrated using noninvasive far-red in vivo imaging. RESULTS: The EGF-MAP selectively induced apoptosis in EGFR-overexpressing proliferating cancer cells through stabilisation of microtubules. Nonproliferating cells were not affected, demonstrating superior selectivity of EGF-MAP for cancer cells. The EGF-MAP was well tolerated at high doses in mice compared with the ETA'-based control. The in vivo efficacy of EGF-MAP was demonstrated in a tumour xenograft mouse model. CONCLUSION: Our data indicate the general mechanism of action for a new class of human immunotherapeutic reagents suitable for the treatment of cancer. This approach combines the binding specificity of targeting ligands with the selective cytotoxicity of MAP towards proliferating cells.